Technical Analysis of Comfort and Energy Consumption in Smart Buildings With Three Levels of Automation: Scheduling, Smart Sensors, and IoT - Rahmat Aazami; Mohammad Moradi; Mohammadamin Shirkhani; Ambe Harrison; Saad F. Al-Gahtani; Z. M. S. Elbarbary (IEEE Access)
Energy consumption and efficiency, along with occupant well-being, are key global challenges across various sectors, especially in the industrial and residential domains. Building automation, which exists at multiple levels, plays a crucial role in addressing these challenges. This study evaluates three distinct levels of automation—scheduling-based, sensor-based, and IoT-enabled control—allowing a clear comparison of each system’s effectiveness in managing energy consumption and enhancing occupant comfort. This approach simplifies the decision-making process by identifying the level of control that optimally balances energy efficiency with thermal comfort requirements, particularly in residential contexts. The integration of the Internet of Things (IoT) into building control systems, a hallmark of the Fourth Industrial Revolution, further enhances these capabilities. Building automation and control systems can be categorized into standard and advanced systems. Conventional control methods fall short of meeting the increasingly complex demands of smart buildings. However, leveraging IoT in smart building design can significantly enhance quality of life by making smart systems more efficient, optimizing resource allocation, and improving management capabilities and services. A key application of IoT in smart buildings is the efficient management of HVAC (heating, ventilation, and air conditioning) systems, which enhances occupant comfort while reducing energy consumption. This paper presents a simulation of a residential building in Ilam, where energy consumption and occupant comfort levels are analyzed across various scenarios. The study identifies optimal conditions for both energy efficiency and resident well-being. By evaluating a residential building, this research compares energy consumption and comfort across basic scheduling, sensor-based control, and advanced IoT-enabled automation levels. Optimal configurations that improve energy savings and occupant comfort are identified, highlighting the effectiveness of IoT integration in HVAC management. The results demonstrate that advanced automation, particularly IoT-based control, offers significant advantages for energy management and comfort optimization in residential buildings.